TEACHING STUDENT’S WRITING SKILL BY USING COLLABORATIVE WRITING STRATEGY IN DESCRIPTIVE TEXT AT NINTH GRADERS OF SMP PLUS DARUSSALAM BLOKAGUNG IN ACADEMIC YEAR 2021/2022 - Moh.Mahmud Mahmud; Firda Afkarina Ali (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
In learning English, writing is one of the important skills that must be learned for students in junior high school. One good strategy that can be used by teachers in English classrooms is the collaborative writing strategy. Collaborative writing strategy is one good strategy to express their ideas and be applied in written form. The research problem is: 1). How is using collaborative is using collaborative writing strategy in descriptive text. 2). what the advantages and disadvantages using collaborative writing strategy in descriptive text. The objectives of this study are: (1) to describe the implementation of the collaborative writing strategy in writing. (2) To find out the advantages and disadvantages for students when the teacher applies the collaborative writing strategy in teaching writing descriptive texts. This study uses a qualitative method that uses descriptive qualitative to analyze data. This research was conducted at ninth graders and ninth grade English teacher SMP Plus Darussalam Blokagung. The findings in this study using collaborative writing in teaching descriptive text have some advantages and disadvantages for students and teachers in teaching descriptive text. First, this strategy can improve writing skills. Secondly, students can easily write descriptive texts in their own words. Third, increase students' feelings and motivation. Also the disadvantages is first, the teacher cannot distinguish between students working on assignments individually or in groups. Second, it is difficult for teachers to know the abilities of each student. Third, it cannot be used with a large number of students.